The Relevance of the Principle of Peace in Islamic Civilization Towards the Israel-Palestine Conflict - Farin Vadila; Vebriana Ika Wulandari; Hasna Sabila Zerlinda (Lembaga Yasin AlSys, 2026)
Although peacebuilding and conflict resolution have been widely discussed in contemporary scholarship, research that systematically connects Islamic civilizational concepts of peace with the ethical challenges of the Israeli-Palestinian conflict remains limited. This study aimed to examine the concept of peace in Islamic civilization and evaluate its relevance as an ethical framework for resolving the Israeli-Palestinian conflict. A qualitative library research design was employed using historical and conceptual approaches. Data were drawn from primary sources, including the Qur’an, hadith, and the Medina Charter, as well as secondary literature on classical Islamic thinkers and contemporary peacebuilding. The findings indicate that Islamic peace is multidimensional, extending beyond the absence of war to include justice (al-‘adl), deliberation (shura), reconciliation (sulh), mediation (tahkim), tolerance (tasammuh), human brotherhood (ukhuwah insaniyah), and universal compassion (rahmatan lil ‘alamin). Historical examples, particularly the Medina Charter and the Treaty of Hudaybiyyah, demonstrate early institutional commitments to pluralism, legal protection, and diplomacy. The study argues that these principles offer normative and practical resources for peace processes by prioritizing long-term justice, civilian protection, inclusive deliberation, and humanitarian solidarity. Applied to the Israeli-Palestinian context, this framework highlights opportunities for moral mediation, human-centered reconciliation, and the involvement of Muslim-majority mediators, while also recognizing constraints such as geopolitical interests, mutual distrust, and extremist distortions of religion. The study concludes that revitalizing and operationalizing Islamic peace values can contribute an alternative ethically grounded pathway toward sustainable peace. Its implications include theoretical contributions to Islamic peace studies and practical relevance for policymakers, religious leaders, and peacebuilding actors in developing multilateral engagement, confidence-building measures, and institutional mechanisms that translate normative principles into political and legal practice.